Tinjauan Tarif AKDP Rute Surabaya-Malang Kelas Ekonomi Akibat Perubahan Harga Solar - Rosida, Ismi Rizkiyani; Agusdini, Theresia Maria Chandra (Institut Teknologi Adhi Tama Surabaya, 2023)
The increase in diesel prices due to subsidized fuel restrictions has an impact on the increase in City Transport Rates within the Province of the Surabaya-Malang economy class route. Unstable world crude oil prices also result in diesel prices can change at any time. Therefore, it is necessary to review the tariff increase from the service provider side, namely vehicle operating costs and estimate the tariff amount if diesel prices change. The tariff calculation based on vehicle operating costs is based on the Decree of the Minister of Transportation Number KM.89 of 2002, while the estimated tariff if the price of diesel changes uses an increase in diesel every 10% of the price of diesel before the increase of Rp 5,150. This is based on the development of diesel prices from the past few years. Based on the calculation of vehicle operating costs, a tariff of IDR 18,915.69 is obtained, the tariff is in accordance with the applicable tariff, which is IDR 20,000, because the calculation rate based on vehicle operating costs is lower than the applicable tariff. And based on the analysis of tariff estimates, at the increase in diesel 10%-40% service providers can use the rates set at the time of research. Meanwhile, at a 50%-100% increase in diesel, service providers must determine new tariffs.